Pattern discovery in bioinformatics - Narasimhan, Giri (Henry Stewart Talks, 2007)
Why pattern discovery?, Sequence patterns: representations and protein sequence, Patterns of DNA-protein interactions, Structure patterns: representations, discovery and applications, Sequence-structure patterns, Designing training sets for supervised discovery, Algorithmic techniques
Reviewed at 2018/02/08